Building skills and capacities in the Costa Rican dairy subsector - Barboza-Arias, Luis (2016)
Productive dynamics of the dairy sector in Costa Rica, underwent significant changes as a result of  its  historical  evolution.  Because  of  these  changes,  institutional  actors  at  different  levels  of  implementation  promoted  the  incorporation  of  innovations,  including  adaptation  processes  to  the  geographical   and   climatic   conditions   of   the   country.   This   study   focuses   on   the   innovation  management of the dairy sector in Costa Rica. Its main goal is to analyze the process of capability  building of the dairy farmers, considering the importance of knowledge management initiatives.  We  use a case studies methology to introduce three specific experiences of innovation and technology  transfer  in  different  places  of  Costa  Rica.  Results  suggest  that  National  System  of  Innovation  of  country  plays a special role in  designing  of strategic  working agenda, however,  key aspects could  enhance  if  knowledge  management  and  capability  buildings  approaches  are  considered. Finally,  the paper concludes that the promoting of community participation mechanisms is important to build  collective   actions   and   setting   up   institutional   dialogues   for   the   inclusive   local   development strategies.